Egyptology in the service of learning chemistry in Industrial Engineering - Javier Gimenez (OmniaScience, 2014)
Ancient cultures or civilizations carried out different technological improvements without the knowledge of the scientific processes involved. At the Escola Tècnica Superior d'Enginyeria Industrial de Barcelona (ETSEIB), some courses deal with the technological achievements in the antiquity and, in particular, one course deals with the achievements of the Ancient Egyptians, not only to learn what the Ancient Egyptians knew and made but also to look for scientific solutions to modern problems related with the antiquity. In this sense, this work considers the teaching of the chemical basis involved in one technological development of the ancient Egyptians which is taught in one Elective Course entitled: "Questions of technology and civilization in the Ancient Egypt". The students use their knowledge on Basic Chemistry as well as on Inorganic and Analytical Chemistry in order to understand the chemistry involved in the technological development carried out at the Bronze Age (3000-1200 BC) and propose solutions to the variation in the colour of the hieroglyphs painted in papyri. The experience acquired in the lessons taught in the Elective Course together with the feed-back from the students is used to implement a new optional course in the Bachelor's Degrees in Industrial Engineering, Chemical Engineering and Materials Engineering named "Technological and Scientific Developments in Antiquity: Ancient Egypt and Middle East and North Africa".